Application of the Locality Approach in History Learning: A Case Study of 'Pamali' Cultural Values in Social Studies Education in West Nusa Tenggara - Denian Sutisnaris; Malik Hidayat (Gema Cendekia Institute, 2025)
This study aims to analyze the application of the locality approach in history learning through the integration of Pamali cultural values in West Nusa Tenggara. The locality approach is seen as a contextual strategy that links the learning process to the socio-cultural environment of students, thereby strengthening the relevance of education to the formation of local identity and character. This study uses a qualitative approach with a case study design carried out in one of the junior high schools in East Lombok Regency. Data was collected through participatory observation, in-depth interviews with teachers and students, and analysis of curriculum documents and lesson plans. The results of the study show that the Pamali values that live in Lombok society, such as the prohibition of actions that damage social harmony and the environment, have great potential in fostering students' moral awareness, discipline, and social responsibility. The integration of these values in history learning provides space for students to understand the meaning of past events contextually and reflectively. In addition to enriching social studies learning content, the application of this locality approach also strengthens the dimension of character education based on local wisdom that is relevant to the spirit of Pancasila and the goals of national education. The implications of this study emphasize the need for curriculum innovation that is responsive to the regional cultural context, in order to create a history learning model that has character, inclusiveness, and is oriented towards strengthening national identity in the global era.